A zebrafish model of congenital nephrotic syndrome of the Finnish type - Lee, Mi-Sun; Devi, Sulochana; He, John Cijiang; Zhou, Weibin (Frontiers in Cell and Developmental Biology, 2022)
Nephrotic syndrome (NS) is a disease characterized by proteinuria and subsequent hypoalbuminemia, hyperlipidemia and edema due to the defective renal glomerular filtration barrier (GFB). Mutations of NPHS1, encoding NEPHRIN, a podocyte protein essential for normal GFB, cause congenital nephrotic syndrome (CNS) of the Finnish type (CNF), which accounts for about 50% of CNS cases. We generated zebrafish nphs1 mutants by using CRISPR/Cas9. These mutants completely lack nephrin proteins in podocytes and develop progressive peri-orbital and whole-body edema after 5 days post fertilization. Ultra-structurally, loss of nephrin results in absence of slit-diaphragms and progressive foot process effacement in zebrafish pronephric glomeruli, similar to the pathological changes in human CNF patients. Interestingly, some nphs1 mutants are viable to adulthood despite ultra-structural defects in renal glomeruli. Using a reporter line Tg (l-fabp:VDBP-GFP) expressing GFP-tagged vitamin-D-binding protein in the blood plasma, we observed a reduction of intravascular GFP fluorescence in the nphs1 mutants, a hypoalbuminemia-like phenotype. In addition, we detected excretion of GFP by the nphs1 mutants, reminiscent of proteinuria. Therefore, we have demonstrated that the nphs1 mutant zebrafish recapitulate the human NS phenotypes and provide a novel and relevant animal model useful for screening therapeutical agents for this disease.